If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4-3(2a+8=-20-8a
We move all terms to the left:
4-3(2a+8-(-20-8a)=0
We add all the numbers together, and all the variables
-3(2a+8-(-8a-20)+4=0
| 20-1/3n=7 | | 10(x-4)-3=47 | | 2x+3/x+7=4/x | | 39-8n=-24-32n+3n | | -3-n=-3(n-1) | | 3(3x+2)=-5(2x-3)-4x | | 4k+5=-(3k+2) | | 3(a+7)=8 | | 24x=1/16 | | (m=2)^2=0 | | 39-8n=-24-32n=3n | | 5x-9=6x-9 | | 5y-3y-6=15.52 | | -6=m+5-6 | | 7x+4(-5x+2)=-70 | | x2+9x-52=0 | | 20+30x=40x | | (10(x-2))/2=5(2x-4) | | 24+6x=-6(-4-x) | | 3x+12=17+2× | | 1-7r=3-3-6r+6 | | 6p-20=-2(-10-6p) | | 4/3(x+1/4)=x+5/9 | | -8.5=1/(4x) | | 0.85x-0.76=7.17-5.25x | | -1x+17-4x=2 | | 0=t^2-14t+30 | | -5(6a+21)=15 | | 31+3x=-1 | | -8x-(3×+6)=4-x | | -15-13v=-15v+5 | | 6x-3=-18=x |